ESTIMATION OF CELECOXIB IN HUMAN PLASMA BY RAPID AND SELECTIVE LC-MS/MS METHOD FOR A BIOEQUIVALENCE STUDY - Patel, Nirav P.; Sanyal, Mallika; Shrivastav, Pranav S.; Patel, Bhavin N. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: A selective, sensitive and rapid liquid chromatography-tandem mass spectrometry (LC-MS/MS) assay has been developed for the determination of celecoxib (CXB) in negative ionization mode. Methods: Celecoxib and celecoxib-D7 (CXB-D7) as internal standard (IS) were extracted from 300 µl human plasma by solid-phase extraction using strata-X SPE cartridges. Chromatographic separation was achieved on ACE C8-300 (50 × 4.0 mm, 3.0 μm) column using methanol-1.0 mmol ammonium acetate solution in 80:20 (v/v) ratio. The protonated precursor to product ion transitions studied for CXB and CXB-D7 were m/z 380.0 → 315.9 and 387.0 → 323.0, respectively. Results: The limit of detection (LOD) and lower limit of quantitation of the method were 2.50 and 10.0 ng/ml respectively with a linear dynamic range of 10.0-4000 ng/ml for CXB. The intra-batch and inter-batch precision (% CV) and mean relative recovery across quality control levels is<7.2 % and 85.5 % respectively. Matrix effect in human plasma, expressed as IS-normalized matrix factor ranged from 0.99-1.03. Conclusion: The method was successfully applied in healthy subjects using a single dose of 400 mg celecoxib capsules under fasting and fed conditions. The reproducibility in the measurement of study data is demonstrated by incurred sample reanalysis.